A framework for incorporating environmental issues into the evaluation of state highway roading projects : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy (Environmental Planning) at Massey University - Stevenson, Megan Anne (Massey University, 1995)
A framework for incorporating environmental issues into the evaluation of State Highway roading alternatives is developed. The steps taken in the research method included: a review of current valuation and evaluation techniques for incorporating environmental issues into the evaluation process; a review of the current State Highway evaluation framework in New Zealand; and a study of two State Highway roading projects. Principal participants in the evaluation process of both case studies were interviewed and a comparative review of the case studies undertaken. An "ideal" evaluation framework was developed during the study. This framework was based on the comparative review of the case studies and an analysis of current practice and techniques. The "ideal" evaluation framework involves Regional Councils, rather than Central Government, controlling the evaluation process and Regional Land Transport Committees making the final decision as to the "best" alignment option. Changes to the Resource Management Act 1991 are recommended to enable a more effective and integrated evaluation process. Such changes include clearly defining "consultation" and increasing the amount of information to be submitted by resource consent applicants. Specifically, applicants would be required to detail the type of evaluation technique used, evidence that the process had been independently reviewed and the findings of the independent review. The "ideal" evaluation framework consists of a detailed planning process comprising 13 integrated phases within four contexts. These contexts are institutional, ecological, socio-economic and engineering. In the second phase of the planning process, community and organisational values are assessed using Focus Groups and Attitude Surveys. This phase determines the limits of each context prior to the evaluation of alternatives. The research demonstrated that the most appropriate and effective evaluation technique for incorporating environmental issues into the evaluation of State Highway roading alternatives is the Goals Achievement Matrix (GAM). Based on the findings of the case study reviews the formation of a Community Group and employment of an independent advisor(s) is recommended. Provided that the "ideal" evaluation framework is based upon the criteria recommended in the study (including effective, appropriate consultation and a clear understanding of who is the final decision-maker), this framework could be used to successfully incorporate environmental issues into the evaluation of State Highway roading alternatives.
Keywords: Road design and construction; Highway relocation; State highway roading, New Zealand; Roads and environment